Believing in dissociative amnesia relates to claiming it: a survey of people's experiences and beliefs about dissociative amnesia. Issue 10 (26th November 2021) - Mangiulli, Ivan; Jelicic, Marko; Patihis, Lawrence; Otgaar, Henry
ABSTRACT: Dissociative amnesia is one of the most controversial categories in the field of psychiatry and clinical psychology. Self-reports of dissociative amnesia in the general population, and beliefs about this topic, have so far not been subjected to empirical scrutiny. Here, we surveyed a sample from the general population ( N  = 1017), revealing that about a tenth ( n  = 102) claimed to have experienced dissociative amnesia. Some claims pertained to amnesia for traumatic autobiographical experiences (e.g., sexual assault), while other claims reflected memory loss for experiences that can be regarded as non-traumatic or non-stressful (e.g., dissociative amnesia for an anniversary). Importantly, many participants believed in the existence of dissociative amnesia, and those who claimed dissociative amnesia indicated even more belief in this phenomenon than the rest of the sample. Finally, many participants indicated to have at least once claimed to have feigned memory loss in their life, and that they experienced some form of forgetting when trying to retrieve events for which they lied upon. Overall, our findings suggest that claiming dissociative amnesia goes hand in hand with believing in dissociative amnesia.